The impact of governance indicators on economic growth “Iraq, a case study for the period (2002-2020)” - Abdel Qader, Kulthum (Humanities Journal of University of Zakho, 2023)
The embodiment of the dimensions of governance is necessary to build a governance based on justice and transparency that ultimately leads to achieving political stability through which corruption and poor regulation can be fought. The application of the mechanism and indicators of governance means ensuring economic stability. Accordingly, the main objective of the current study was to measure the impact of governance indicators on economic growth in Iraq, during the period (2002-2020). This is done by estimating the multiple regression equation using the ordinary least squares method. The research concluded that the error correction limit coefficient was significant and negative, reaching (-0.156, which means that (15.6%) of the imbalances of economic growth are corrected during one quarter in the long term. The results of the assessment also showed that All indicators of governance had a significant and negative impact on the Iraqi economic growth during the research period, and all of them were contrary to the logic of economic theory, with the exception of the indicator and control of corruption, as the results showed that it affects negatively and morally on economic growth .A number of proposals were presented, including: In-depth institutional reforms that include all economic and political institutions in order to combat and eliminate corruption.